High-Temperature Cavity Receiver Integrated with a Short-Term Storage System for Solar MGTs: Heat Transfer Enhancement. (September 2017) - Giovannelli, A.; Bashir, M.A.
Abstract: Dish-Micro Gas Turbines (MGTs) can be promising systems for power production at small-scale by concentrated solar radiation. Several high-temperature solar receivers have been already designed for such plants, however, nowadays, none of them can assure the proper thermal inertia to level the effects of solar radiation fluctuations on engine performance and safety. In this paper, a solar receiver integrated with a short-term storage system based on high-temperature Phase-Change Materials (PCMs), is proposed. On the basis of a previous preliminary component design and analysis, the receiver geometry has been modified to improve storage capability and heat transfer to the working fluid, reducing temperatures on the irradiated surface making them compatible with material properties and reducing also temperature gradients inside the PCM. Six different geometries, varying length, opening and shape of a front cavity have been analyzed by means of CFD methods. All the configurations have shown a satisfactory behavior in terms of working fluid outlet temperature, storage capabilities and maximum temperatures reached on the surface and inside the receiver. In particular, among them, three geometries can be considered the most promising ones.